2023
DOI: 10.3390/genes14040867
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of NLR Genes Reveals Divergent Evolution on NLRome in Diploid and Polyploid Species in Genus Trifolium

Abstract: Crop wild relatives contain a greater variety of phenotypic and genotypic diversity compared to their domesticated counterparts. Trifolium crop species have limited genetic diversity to cope with biotic and abiotic stresses due to artificial selection for consumer preferences. Here, we investigated the distribution and evolution of nucleotide-binding site leucine-rich repeat receptor (NLR) genes in the genus of Trifolium with the objective to identify reference NLR genes. We identified 412, 350, 306, 389 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Duplication and polyploidization are significant contributors to plant speciation and divergence as they result in the creation of novel gene functions, and neo-functionalization of duplicated genes as well as recombination [66]. Furthermore, transpositions and structural variation might also play a role in the divergent evolution of genes [67]. Genome-wide studies of various gene families in Brassicaceae have consistently indicated their expansion compared with Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Duplication and polyploidization are significant contributors to plant speciation and divergence as they result in the creation of novel gene functions, and neo-functionalization of duplicated genes as well as recombination [66]. Furthermore, transpositions and structural variation might also play a role in the divergent evolution of genes [67]. Genome-wide studies of various gene families in Brassicaceae have consistently indicated their expansion compared with Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Extinction of pathogen often lead to death of several NLR genes to maintain host fitness [ 33 ]. Among Fabaceae family, several members have been investigated including Dalbergioids , genus Cicer and genus Trifolium [ 22 , 32 , 37 ]. One common observation, was the importance of crop wild relatives (CWRs) that contain broader and expanded NLRome and conversely domesticated crop species suffers from narrowing of genetic diversity [ 22 , 32 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among Fabaceae family, several members have been investigated including Dalbergioids , genus Cicer and genus Trifolium [ 22 , 32 , 37 ]. One common observation, was the importance of crop wild relatives (CWRs) that contain broader and expanded NLRome and conversely domesticated crop species suffers from narrowing of genetic diversity [ 22 , 32 , 37 ]. Secondly, presence of polyploidy have considerably broaden and expanded the NLRome of allotetraploid species of Arachis and Trifolium [ 22 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations